Contact Binaries on Their Way Towards Merging - Gazeas, K. (2015)
Contact binaries are the most frequently observed type of eclipsing star system. They are small, cool, low-mass binaries belonging to a relatively old stellar population. They follow certain empirical relationships that closely connect a number of physical parameters with each other, largely because of constraints coming from the Roche geometry. As a result, contact binaries provide an excellent test of stellar evolution, specifically for stellar merger scenarios. Observing campaigns by many authors have led to the cataloging of thousands of contact binaries and enabled statistical studies of many of their properties. A large number of contact binaries have been found to exhibit extraordinary behavior, requiring follow-up observations to study their peculiarities in detail. For example, a doubly-eclipsing quadruple system consisting of a contact binary and a detached binary is a highly constrained system offering an excellent laboratory to test evolutionary theories for binaries. A new observing project was initiated at the University of Athens in 2012 in order to investigate the possible lower limit for the orbital period of binary systems before coalescence, prior to merging.